Fabrication and Characterization of Physical, Mechanical, and Wear Characteristics of AA7075/SiC Composites by Floating Die - Ameen Al Njjar; Kamar Mazloum; Amit Sata (Tribology in Industry)
The study investigates AA7075-based matrix composites, renowned for their strength and wear resistance, with a focus on aerospace and automotive applications. Using powder metallurgy with floating die-pressing, composites with varying SiC weight proportions (0%, 5%, 10%, 15%) were synthesized and thoroughly analyzed for physical, mechanical, and microstructural properties. Through L9 orthogonal array experiments, the effects of SiC weight percentage, sliding distance, load, and sliding speed on tribological behavior were studied, employing Taguchi's analysis and ANOVA to understand and quantify these effects. Regression equations, contour plots, and surface plots generated using the response surface method helped visualize the relationships between these factors. The composite containing 5% SiC demonstrated superior properties, including a substantial increase in compressive strength (20.1%), weight reduction (13.7%), and a significant decrease in wear loss (83.28%), making it highly promising for aerospace, defense, and automotive sectors. Additionally, uniform failure models were observed in compression tests of composites fabricated using the floating die method. ANOVA analysis revealed that wear loss was primarily influenced by sliding distance (77.13%), followed by SiC weight percentage (11.77%), sliding speed (9.68%), and load (1.42%). The coefficient of friction (COF) was affected by SiC weight percentage (47.54%), followed by sliding distance (22.72%), load (19.14%), and sliding speed (10.59%).